Aerogel applied to electromagnetic shielding and preparation method thereof
By interspersing titanium dioxide nanowires on the graphene oxide sheet layer to construct aerogel materials with layered sheet structures, the problems of insufficient mechanical stability and electromagnetic shielding capabilities of existing electromagnetic wave absorbing materials in complex environments are solved, and efficient, flexible and lightweight electromagnetic shielding effects are achieved.
Patent Information
- Application Number
- CN202411814045.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-10
- Publication Date
- 2025-03-14
AI Technical Summary
The existing electromagnetic wave absorbing materials have defects such as high density, easy corrosion, and difficult processing, and it is difficult to maintain mechanical stability and excellent electromagnetic shielding capabilities in complex environments.
Layer flake-like structure aerogel materials constructed with titanium dioxide nanowires interspersed on graphene oxide sheets are prepared by hydrothermal reaction, ultrasonic mixing and directional freeze-drying to form an aerogel with a cross-dimensional structure.
It achieves the maintenance of extreme mechanical stability and excellent electromagnetic shielding ability in complex environments. It has low material density, good flexibility and easy processing, and is suitable for a variety of electromagnetic shielding scenarios.
Smart Images

Figure CN119629978A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to aerogel preparation technology, and in particular to an aerogel used for electromagnetic shielding and a preparation method thereof. Background Art
[0002] Network security is the key to ensuring the normal and efficient operation and maintenance of information in the wave of informatization. As the basic support and barrier of network security, electromagnetic safety is becoming more and more important. 5G mobile communication technology is increasingly widely used in civil infrastructure scenarios such as the Internet of Things, Internet of Vehicles, and other Internet of Everything, wireless Internet, etc. Traditional electromagnetic wave absorbing materials have defects such as high density, easy corrosion, and difficult processing. Therefore, it is urgent to develop an electromagnetic shielding material with low density and mechanical stability.
[0003] Aerogel material is a gel material whose dispersion medium is gas. It has a porosity of 80-99.8%, a density as low as 3kg / m3, and a room temperature thermal conductivity as low as 0.012W / m·k. It has low density and heat insulation and temperature resistance, showing great potential to meet the high requirements of electromagnetic wave absorption materials.
[0004] Traditional aerogel materials are mostly pearl necklace-like structures formed by the accumulation of nanoparticles. Aerogel materials with this structure are brittle and often suffer from severe strength degradation and structural collapse under large mechanical stress or thermal shock. Nanowire aerogels are composed of nanowires with a high aspect ratio, which have excellent mechanical properties while being resistant to high temperatures. In addition, the sparse connections and fragile nodes inside the nanowire aerogels result in low intrinsic conductivity of the aerogels, and they are difficult to adapt to complex deformations in many extreme applications, which in turn limits further development.
[0005] Two-dimensional graphene oxide has the characteristics of large specific surface area, high thermal conductivity and good dielectric loss, but the dielectric loss of pure graphene oxide is large, which easily causes impedance mismatch and cannot meet the requirements of high-performance microwave absorbing materials. Titanium dioxide is an ultra-light material with dielectric loss. Although it has poor conductivity, it can effectively adjust the dielectric constant of carbon-based materials and produce additional interface interactions, making the material show greater dielectric loss and efficient microwave absorption.
[0006] Therefore, it is crucial to develop a flexible, ultra-lightweight, highly stable aerogel material and a preparation method thereof that can maintain extreme mechanical stability in complex environments and have excellent electromagnetic shielding capabilities for use in electromagnetic wave absorption.
[0007] "Preparation and Performance Study of Aerogel Visible Light Responsive Photocatalysts" (Li Suyan et al., Journal of Tianjin University of Technology, Vol. 39, No. 6, December 2023) Using GO (graphene oxide) and TiO2 under certain conditions to form an aerogel composite porous material can significantly improve the photocatalytic performance of nano TiO2.
[0008] Chinese invention patent application CN 109517562 A provides a ceramic conductive adhesive for electronic packaging and a preparation method thereof. By cross-linking and coating modification of titanium diboride, the volume resistivity of the titanium diboride ceramic conductive adhesive is significantly reduced and the conductivity is improved.
[0009] However, neither of them has formed a cross-dimensional structure constructed with nanowires and two-dimensional graphene oxide, nor has it targeted the field of electromagnetic shielding, and neither has disclosed the process conditions related to electromagnetic shielding. Summary of the invention
[0010] In response to the above problems, the present invention proposes a flexible, ultra-lightweight, highly stable aerogel material and a preparation method thereof, which can maintain extreme mechanical stability in complex environments and has excellent electromagnetic shielding capabilities.
[0011] The aerogel used for electromagnetic shielding of the present invention has a layered sheet structure, and the layered sheet structure is formed by titanium dioxide nanowires interlaced on graphene oxide sheets as building blocks.
[0012] A method for preparing aerogel for electromagnetic shielding, the steps comprising:
[0013] The titanium dioxide nanopowder is mixed with an alkaline solution, and a mixed solution is obtained by stirring and ultrasonication;
[0014] placing the mixed solution in a sealed container for hydrothermal reaction to obtain a nanowire gel;
[0015] Mixing the graphene oxide nanosheet dispersion and the acidic solution and adding them to the nanowire gel, and mixing them thoroughly by ultrasound to obtain a suspension;
[0016] The suspension is subjected to directional freezing and freeze drying to obtain the aerogel.
[0017] Furthermore, after obtaining the aerogel, heat treatment is performed.
[0018] Furthermore, the heat treatment is heating in an air atmosphere at a temperature of 150-250° C. for a treatment time of 0.5-2 h.
[0019] Furthermore, the concentration of the alkaline solution is 8M to 12M, the mass ratio of the titanium dioxide nanopowder to the alkaline solution is 1:9 to 1:199, and the stirring and ultrasound are specifically stirring in a homogenizer for 30 minutes to 60 minutes.
[0020] Furthermore, the hydrothermal reaction is specifically to pour the mixed solution into a polytetrafluoroethylene container, put it into a reaction kettle, and place it in an oven at 120-180° C. for 36 h to 48 h.
[0021] Furthermore, the volume fraction of the acidic solution is 1% to 5%, the concentration of the graphene oxide nanosheet dispersion is 5-20 mgmL-1, and the mass ratio of the nanowire gel, the graphene oxide nanosheet dispersion and the acidic solution is 1:1:1 to 1:1:3.
[0022] Furthermore, the ultrasonic mixing is performed by using a cell crusher to mix evenly, with an ultrasonic power of 50-100 W and an ultrasonic time of 0.6-1 h.
[0023] Furthermore, the directional freezing and freeze drying use a self-made directional freezing mold made of PDMS and metal plates, the pressure of the freeze dryer is set to 1-10Pa, the temperature is -50--60°C, and the freeze drying is performed for 48-72h.
[0024] Furthermore, the alkaline solution is a sodium hydroxide solution, and the acidic solution is an acetic acid solution.
[0025] The beneficial effects of the present invention are as follows:
[0026] Compared with traditional electromagnetic shielding materials, the present invention has obvious advantages such as flexibility, light weight, controllable structure and easy processing.
[0027] The nanowires constructed by the present invention are interspersed on the graphene oxide sheets, which effectively prevents the aggregation of the graphene sheets, is conducive to the formation of a conductive network between the graphene sheets, improves the electron migration efficiency, and gives the titanium dioxide composite material excellent conductive properties.
[0028] The aerogel material prepared by the present invention has a cross-dimensional structure constructed by nanowires and two-dimensional graphene oxide, generates dipole polarization or interface polarization loss under an alternating electric field, and exhibits excellent electromagnetic response and loss capacity.
[0029] The preparation method adopted by the present invention has excellent flexibility compared with aerogels prepared by traditional sol-gel and supercritical drying. The size and thickness of the aerogel can be changed according to the needs of electromagnetic shielding scenarios, and the designability is very strong.
[0030] The density of the aerogel material prepared by the present invention can be as low as 0.018 g / cm3, and compared with other low-density aerogel materials of the same strength, it has the characteristic of being ultra-lightweight.
[0031] The aerogel material prepared by the present invention has good flexibility, can be quickly restored to any shape after being bent, and has no damage to the structure after multiple cycles of deformation, and has excellent conformability.
[0032] The preparation process of the present invention adopts a directional freezing-freeze drying method, which reduces the preparation cost and improves the efficiency compared with the traditional drying method of aerogels - supercritical drying.
[0033] The present invention adopts an alkaline solution phase as a reaction medium, so that the functionalized carbon nanotubes have good dispersibility, and solves the problem that the carbon nanotubes are easy to agglomerate.
[0034] The excellent mechanical stability of the aerogel material prepared by the present invention solves the contradiction between the low density and large volume of ultra-light aerogel materials, greatly reduces the transportation and use costs of the materials, and lays a foundation for its industrial development.
[0035] The aerogel material prepared by the present invention has a directional network structure constructed by nanowires and two-dimensional graphene sheets, and has the characteristic of not falling off powder compared with the pearl necklace-like structure formed by nanoparticles piled up by the traditional solution-gel method.
[0036] The aerogel material prepared by the method of the present invention exhibits excellent environmental tolerance and can maintain stable electromagnetic shielding capability after being subjected to extreme environments such as mechanical compression, high and low temperatures, etc. BRIEF DESCRIPTION OF THE DRAWINGS
[0037] Figure 1 is a flow chart of an embodiment of the present invention.
[0038] Figure 2 is a SEM image of the aerogel prepared according to the embodiment of the present invention.
[0039] Figure 3 It is the electromagnetic shielding effectiveness curve of the aerogel prepared by the present invention in the X-band.
[0040] Figure 4 The figure is a comparison of the electromagnetic shielding effectiveness of the aerogels prepared by the present invention during the compression process. DETAILED DESCRIPTION
[0041] In order to make the purpose, technical solution and advantages of the present invention clearer, the technical solution of the present invention will be clearly and completely described below in combination with the embodiments of the present invention. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.
[0042] The present invention provides a method for preparing an aerogel for electromagnetic shielding. Figure 1 As shown, the method includes the following steps.
[0043] (1) Titanium dioxide nanopowder and alkaline solution are mixed in deionized water, and a mixed solution is obtained by stirring and ultrasonication.
[0044] The specific steps are as follows: dissolve titanium dioxide nanopowder with a diameter of 10-100nm in water, then add sodium hydroxide solution with a concentration of 8M-12M, and the mass fraction of titanium dioxide nanopowder in the obtained suspension is 0.5%-10%. After mixing, stir in a homogenizer for 30min-60min to obtain a mixed solution.
[0045] (2) placing the mixed solution in a sealed container for hydrothermal reaction to obtain nanowire gel.
[0046] The specific steps are as follows: pour the mixed solution into a polytetrafluoroethylene container, put it into a reactor, and place it in an oven at 120-180°C for 36-48 hours to obtain nanowire gel. This process needs to be carried out under fully closed conditions, and the container material needs to be a polymer material that does not react with the system.
[0047] (3) adding the acidic solution and the graphene oxide nanosheet dispersion into the above gel, and mixing them thoroughly by ultrasonication to obtain a suspension.
[0048] The specific steps are as follows: adding 1% to 5% acetic acid solution and 5-20mgmL-1 graphene oxide nanosheet dispersion to the above nanowire gel, and using a cell crusher to fully and evenly mix with ultrasound, with an ultrasound power of 50-100W and an ultrasound time of 0.5-1h to obtain a suspension. The mass ratio of the nanowire gel, the graphene oxide nanosheet dispersion and the acidic solution is 1:1:1 to 1:1:3.
[0049] (4) Directional freezing and freeze-drying of the suspension to obtain an aerogel having a layered sheet structure in which elastic nanowires are interspersed in a two-dimensional sheet structure as a building block.
[0050] The specific steps are as follows: directional freezing uses a homemade directional freezing mold made of PDMS and metal plates, the pressure of the freeze dryer is set to 1-10Pa, the temperature is -50--60°C, and the freeze drying is performed for 48-72h.
[0051] (5) The aerogel is subjected to heat treatment at a temperature of 150-250° C. in an air atmosphere for a treatment time of 0.5-2 h.
[0052] The embodiments of the present invention take into account that different experimental parameters will inevitably affect the properties of the aerogel, and therefore the optimal parameters are explored through the following examples.
[0053] Example 1
[0054] (1) Titanium dioxide nanopowder and alkaline solution are mixed in deionized water, and a mixed solution is obtained by stirring and ultrasonication.
[0055] The specific steps are as follows: dissolve titanium oxide nanopowder with a diameter of 10-50 nm in 300 g of water, add 150 g of 10M sodium hydroxide solution, and the mass fraction of the nanopowder in the mixed solution is 1%. After mixing, stir in a homogenizer for 60 minutes.
[0056] (2) placing the mixed solution in a sealed container for hydrothermal reaction to obtain an unformed gel.
[0057] The specific steps are as follows: pour the mixed solution into a polytetrafluoroethylene container, put it into a reactor, and place it in an oven at 150°C for 36 hours to obtain a sodium titanate nanowire wet gel. The reaction needs to be carried out under fully closed conditions, and the container material needs to be a polymer material that does not react with the system.
[0058] (3) adding the acidic solution and the graphene oxide nanosheet dispersion into the gel to obtain a dispersion, and mixing them thoroughly by ultrasound to obtain a suspension.
[0059] The specific steps are as follows: add 1% acetic acid solution and 10mgmL-1 graphene oxide nanosheet dispersion to the above nanowire gel, and use a cell crusher to fully and evenly mix with ultrasound, with an ultrasound power of 60W and an ultrasound time of 30min to obtain a suspension. The mass ratio of nanowire gel, graphene oxide nanosheet dispersion and acidic aqueous solution is 1:1:3.
[0060] (4) The suspension obtained in step (3) is subjected to directional freezing and freeze-drying steps to obtain an ultra-stable, lightweight, flexible aerogel material of graphene oxide composite titanium dioxide nanowires.
[0061] The specific steps are as follows: directional freezing uses a homemade directional freezing mold made of PDMS and metal plates, the pressure of the freeze dryer is set to 4Pa, the temperature is -55°C, and freeze drying is performed for 60h.
[0062] (5) The aerogel is heat treated in an air atmosphere at a temperature of 200° C. for a time of 1 h.
[0063] like Figure 2 As shown, the aerogel material with a cross-dimensional heterogeneous structure prepared in Example 1 has excellent flexibility. The electromagnetic shielding performance and stability test of the aerogel material with a cross-dimensional heterogeneous structure in Example 1 found that the flexible aerogel material with a heterogeneous structure exhibited excellent electromagnetic shielding performance. The experimental results are as follows Figure 3 As shown, the electromagnetic shielding effectiveness reaches 64.1 dB. In addition, the aerogel prepared in Example 1 exhibits excellent environmental tolerance and can maintain stable electromagnetic shielding capability after 100 cycles of mechanical compression. Figure 4 Other performance indicators are shown in Table 1.
[0064] Example 2
[0065] (1) Titanium dioxide nanopowder and alkaline solution are mixed in deionized water, and a mixed solution is obtained by stirring and ultrasonication.
[0066] The specific steps are as follows: dissolve titanium oxide nanopowder with a diameter of 10-50 nm in water, then add 8M sodium hydroxide solution, the nanopowder accounts for 0.5% of the mass fraction of the obtained suspension, and stir in a homogenizer for 40 minutes after mixing.
[0067] (2) placing the mixed solution in a sealed container for hydrothermal reaction to obtain an unformed gel.
[0068] The specific steps are as follows: the mixed solution is poured into a polytetrafluoroethylene container, and then placed in a reactor, and placed in an oven at 180°C for 36 hours, and after the insulation is completed, a sodium titanate nanowire wet gel is obtained. The specific steps are as follows: the reaction needs to be carried out under fully closed conditions, and the container material needs to be a polymer material that does not react with the system.
[0069] (3) adding the acidic solution and the graphene oxide nanosheet dispersion into the gel to obtain a dispersion, and mixing them thoroughly by ultrasound to obtain a suspension.
[0070] The specific steps are as follows: add 1% acetic acid solution and 5mgmL-1 graphene oxide nanosheet dispersion to the above nanowire gel, and use a cell crusher to fully and evenly mix with ultrasound, with an ultrasound power of 50W and an ultrasound time of 0.5h to obtain a suspension. The mass ratio of nanowire gel, graphene oxide nanosheet dispersion and acidic aqueous solution is 1:1:1.
[0071] (4) The suspension obtained in step (3) is subjected to directional freezing and freeze-drying steps to obtain an ultra-stable, lightweight, flexible aerogel material of graphene oxide composite titanium dioxide nanowires.
[0072] The specific steps are as follows: directional freezing uses a homemade directional freezing mold made of PDMS and metal plates, the pressure of the freeze dryer is set to 1Pa, the temperature is -50°C, and freeze drying is performed for 48h.
[0073] (5) The aerogel is heat treated at a temperature of 250° C. and a treatment time of 0.5 h in an air atmosphere.
[0074] The aerogel material with a cross-dimensional heterogeneous structure prepared in Example 2 has excellent flexibility. The thermal insulation performance and electromagnetic shielding performance of the aerogel material with a cross-dimensional heterogeneous structure in Example 2 were tested, and it was found that the surface of the flexible aerogel material with a heterogeneous structure had no gloss loss, no discoloration, and no falling off. Other performance indicators are shown in Table 1.
[0075] Example 3
[0076] (1) Titanium dioxide nanopowder and alkaline solution are mixed in deionized water, and a mixed solution is obtained by stirring and ultrasonication.
[0077] The specific steps are as follows: dissolve titanium oxide nanopowder with a diameter of 10-50 nm in water, then add 12M sodium hydroxide solution, the nanopowder accounts for 10% of the mass fraction of the obtained suspension, and stir in a homogenizer for 60 minutes after mixing.
[0078] (2) placing the mixed solution in a sealed container for hydrothermal reaction to obtain an unformed gel.
[0079] The specific steps are as follows: the mixed solution is poured into a polytetrafluoroethylene container, and then placed in a reactor, and placed in an oven at 120°C for 48 hours, and after the insulation is completed, a sodium titanate nanowire wet gel is obtained. The specific steps are as follows: the reaction needs to be carried out under fully closed conditions, and the container material needs to be a polymer material that does not react with the system.
[0080] (3) adding the acidic solution and the graphene oxide nanosheet dispersion into the gel to obtain a dispersion, and mixing them thoroughly by ultrasound to obtain a suspension.
[0081] The specific steps are as follows: add 5% acetic acid solution and 20mgmL-1 graphene oxide nanosheet dispersion to the above nanowire gel, and use a cell crusher to fully and evenly mix with ultrasound, with an ultrasound power of 100W and an ultrasound time of 1h to obtain a suspension. The mass ratio of nanowire gel, graphene oxide nanosheet dispersion and acidic aqueous solution is 1:1:1.
[0082] (4) The suspension obtained in step (3) is subjected to directional freezing and freeze-drying steps to obtain an ultra-stable, lightweight, flexible aerogel material of graphene oxide composite titanium oxide nanowires.
[0083] The specific steps are as follows: directional freezing uses a homemade directional freezing mold made of PDMS and metal plates, the pressure of the freeze dryer is set to 10Pa, the temperature is -60℃, and freeze drying is performed for 72h.
[0084] (5) The aerogel is heat treated at a temperature of 150° C. and a treatment time of 2 h in an air atmosphere.
[0085] The aerogel material with a cross-dimensional heterogeneous structure prepared in Example 3 has excellent flexibility. The thermal insulation performance and electromagnetic shielding performance of the aerogel material with a cross-dimensional heterogeneous structure in Example 3 were tested, and it was found that the surface of the flexible aerogel material with a heterogeneous structure had no gloss loss, no discoloration, and no falling off. Other performance indicators are shown in Table 1.
[0086] Example 4
[0087] Example 4 is substantially the same as Example 1, except that: in the preparation process of the suspension in step 3, no graphene oxide dispersion is added to obtain pure titanium dioxide aerogel material.
[0088] The electromagnetic shielding performance of the aerogel material prepared in Example 4 was tested, and it was found that the electromagnetic shielding effectiveness was 0. Other performance indicators are shown in Table 1.
[0089] Example 5
[0090] Example 5 is basically the same as Example 1, except that: during the preparation of the suspension in step 3, the concentration of the graphene oxide dispersion is changed to 5 mg mL-1, and a composite aerogel material with a cross-dimensional heterogeneous structure is prepared.
[0091] The electromagnetic shielding effectiveness of the composite aerogel in Example 5 is lower than that in Example 1. Other performance indicators are shown in Table 1.
[0092] Example 6
[0093] Example 6 is substantially the same as Example 1, except that during the preparation of the suspension in step 3, only 2% of the mass of the graphene oxide dispersion of the total solution is added.
[0094] The electromagnetic shielding effectiveness of the nano-aerogel material in Example 6 is very low, and other performance indicators are shown in Table 1.
[0095] Example 7
[0096] Example 7 is substantially the same as Example 1, except that during the preparation of the dispersion in step 3, a carbon nanotube dispersion having a concentration of 10 mg mL-1 is added instead of the graphene oxide nanosheet dispersion.
[0097] The output voltage of the composite aerogel in Example 7 is lower than the electromagnetic shielding effectiveness of Example 1. Other performance indicators are shown in Table 1.
[0098] Example 8
[0099] Example 8 is basically the same as Example 1, except that the temperature in the hydrothermal reaction in step 2 is 200° C., and the formed nanowire aerogel material is directly obtained.
[0100] The titanium dioxide in a completely gelled state prepared in Example 8 cannot be mixed with graphene oxide, and a composite aerogel material with a cross-dimensional heterogeneous structure cannot be prepared, because the titanium dioxide has grown into a fully formed gel block at a high hydrothermal temperature, and cannot be mixed with an acidic solution or graphene oxide. Other performance indicators are shown in Table 1.
[0101] Example 9
[0102] Example 9 is basically the same as Example 1, except that: in step 2, the hydrothermal reaction time is 10 hours to obtain an aerogel material.
[0103] The thermal insulation and electromagnetic shielding performance tests of the nano-aerogel material of Example 9 showed that the aerogel was pulverized and the electromagnetic shielding performance was weakened. Because of the short time, the aerogel had not yet grown into a nanowire structure. The entire formation process was that the nanoparticles first grew into nanosheets, and then the nanosheets were etched into nanowires. Other performance indicators are shown in Table 1.
[0104] Example 10
[0105] Example 10 is substantially the same as Example 1, except that in step 4, the aerogel material is directly frozen in a refrigerator to obtain the aerogel material.
[0106] The surface of the aerogel material in Example 10 is rough, the pore distribution is uneven, and the number of macropores visible to the naked eye increases. In Example 1, directional freezing is that ice crystals squeeze the solute along a fixed growth direction, and then the ice crystals sublimate to leave a brick-mud network structure with a fixed direction. However, refrigerator freezing has no direction and a messy structure. On the other hand, the refrigerator freezing temperature is low, more holes are formed, and the structure is more unstable. Other performance indicators are shown in Table 1.
[0107] Embodiment 11
[0108] Example 11 is basically the same as Example 1, except that the freeze-drying process in step 4 is not performed, and normal pressure drying is performed instead to obtain an aerogel material.
[0109] The aerogel material in Example 11 has large shrinkage, cracks, and high density. Other performance indicators are shown in Table 1.
[0110] Table 1:
[0111]
[0112]
[0113] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or make equivalent replacements for some of the technical features therein. However, these modifications or replacements do not deviate the essence of the corresponding technical solutions from the spirit and scope of the technical solutions of the embodiments of the present invention.
Claims
1. An aerogel used for electromagnetic shielding, having a layered sheet structure, wherein the layered sheet structure is formed by titanium dioxide nanowires interlaced on graphene oxide sheets as building blocks.
2. A method for preparing aerogel for electromagnetic shielding: The titanium dioxide nanopowder is mixed with an alkaline solution, and a mixed solution is obtained by stirring and ultrasonication; placing the mixed solution in a sealed container for hydrothermal reaction to obtain a nanowire gel; Mixing the graphene oxide nanosheet dispersion and the acidic solution and adding them to the nanowire gel, and mixing them thoroughly by ultrasound to obtain a suspension; The suspension is subjected to directional freezing and freeze drying to obtain the aerogel.
3. The method according to claim 2, characterized in that After obtaining the aerogel, heat treatment is further performed.
4. The method according to claim 3, characterized in that The heat treatment is performed in an air atmosphere at a temperature of 150-250° C. for a treatment time of 0.5-2 h.
5. The method according to claim 2, characterized in that: The concentration of the alkaline solution is 8M to 12M, the mass ratio of the titanium dioxide nanopowder to the alkaline solution is 1:9 to 1:199, and the stirring and ultrasound are specifically stirring in a homogenizer for 30 minutes to 60 minutes.
6. The method according to claim 2, characterized in that The hydrothermal reaction is specifically to pour the mixed solution into a polytetrafluoroethylene container, put it into a reaction kettle, and place it in an oven at 120-180° C. for 36 h to 48 h.
7. The method according to claim 2, characterized in that The volume fraction of the acidic solution is 1% to 5%, the concentration of the graphene oxide nanosheet dispersion is 5-20 mg mL-1, and the mass ratio of the nanowire gel, the graphene oxide nanosheet dispersion and the acidic solution is 1:1:1 to 1:1:
3.
8. The method according to claim 2, characterized in that: The ultrasonic mixing is performed thoroughly and uniformly using a cell crusher, with an ultrasonic power of 50-100 W and an ultrasonic time of 0.6-1 h.
9. The method according to claim 2, characterized in that: The directional freezing and freeze drying adopts a self-made directional freezing mold made of PDMS and metal plates, the pressure of the freeze dryer is set to 1-10Pa, the temperature is -50--60°C, and the freeze drying is performed for 48-72h.
10. The method according to claim 2, characterized in that The alkaline solution is a sodium hydroxide solution, and the acidic solution is an acetic acid solution.
Citation Information
Patent Citations
Ceramic conductive adhesive for electronic packaging and preparation method of ceramic conductive adhesive
CN109517562A